Linguistic biomarkers of dementia in Italian patients living in Lombardy: insights from NLP analysis - Maria Letizia Piccini Bianchessi; Gloria Gagliardi (Linguistik Online)
Nowadays, dementia poses a major challenge for healthcare services, with consequences on both the economic and the organizational front. The number of people affected by this disease is steadily increasing, and existing pharmacological and psycho-social therapies only aim to slow its progression. Therefore, a timely diagnosis is crucial for early intervention. For this reason, researchers from different disciplines are trying to find the “biomarkers” of dementia to obtain a detailed profiling of this disease and its etiology. In particular, great attention has been directed towards language, as it is one of the first cognitive domains affected by the pathology. The new frontier in the analysis of spoken language productions is the employment of Natural Language Processing (NLP) techniques and Artificial Intelligence (AI), as they enable an ecological and non-intrusive detection of dementia.